1988
DOI: 10.1021/bi00420a006
|View full text |Cite
|
Sign up to set email alerts
|

Stability and covalent modification of P-glycoprotein in multidrug-resistant KB cells

Abstract: An antipeptide antibody (P7) to P-glycoprotein has been produced by immunizing rabbits with a synthetic peptide. Antibody P7 is directed against the amino-terminal region of P170 (residues 28-35). The antibody immunoprecipitates a 170-kDa P-glycoprotein from extracts of drug-resistant KB-V1 cells that is not present in the drug-sensitive cell line KB-3-1. Antibody P7 was used to quantitate the amount of P-glycoprotein present in drug-resistant KB lines at various levels of resistance and to demonstrate the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
50
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(57 citation statements)
references
References 40 publications
6
50
1
Order By: Relevance
“…The seminal manuscript that gave P-gp its name relied on detecting the protein in drug-resistant CHO cell membranes by virtue of its glycosylation status (Juliano and Ling, 1976). Further studies on its glycosylation status indicated that P-gp was synthesized as a 140-kDa precursor that was glycosylated over a 2-to 4-hour period to its fully mature form that migrated as a broad band at 180 kDa in SDS-PAGE (Richert et al, 1988;Yoshimura et al, 1989). Two investigations demonstrated that in the drug-resistant human KB cell line, P-gp was markedly stable, with a half-life greater than 24 hours (Richert et al, 1988;Yoshimura et al, 1989).…”
Section: Altered Expression Of P-gpmentioning
confidence: 99%
“…The seminal manuscript that gave P-gp its name relied on detecting the protein in drug-resistant CHO cell membranes by virtue of its glycosylation status (Juliano and Ling, 1976). Further studies on its glycosylation status indicated that P-gp was synthesized as a 140-kDa precursor that was glycosylated over a 2-to 4-hour period to its fully mature form that migrated as a broad band at 180 kDa in SDS-PAGE (Richert et al, 1988;Yoshimura et al, 1989). Two investigations demonstrated that in the drug-resistant human KB cell line, P-gp was markedly stable, with a half-life greater than 24 hours (Richert et al, 1988;Yoshimura et al, 1989).…”
Section: Altered Expression Of P-gpmentioning
confidence: 99%
“…1-3). P-glycoprotein was described as a phosphoglycoprotein (9,10), and several studies have corroborated that both native and recombinant P-glycoproteins are phosphorylated in vivo (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Numerous studies have been conducted to address the importance of phosphorylation for the multidrug transporter activity of P-glycoprotein.…”
Section: Multidrug Resistance (Mdr)mentioning
confidence: 99%
“…In addition to these concepts, we think that post-translational modifications of ABC transporters, specifically glycosylation, is an important field of reasearch 6 through which new insights into the function of ABC transporters in tumorigenesis should be forthcoming. That glycosylation defects on ABC transporters, in particular ABCC1 (also known as MRP1), have consequences has been provided by a study showing the mislocalization of multidrug transporters in cisplatin-resistant cancer cell lines 7 .…”
mentioning
confidence: 99%